THE EFFECT OF HORMONAL CONTRACEPTION ON OBESITY IN WOMEN OF REPRODUCTIVE AGE IN JAKARTA, INDONESIA - Hamidah; Heri Rosyati; Asry Novi (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Hormonal contraception can stimulate the appetite control center in the hypothalamus, so that acceptors eat more than usual. The use of hormonal contraception in women of childbearing age can lead to weight gain which can lead to obesity. Obesity in women of childbearing age will increase the risk of developing diseases such as diabetes, hypertension, hyperlipidemia, and preeclampsia during pregnancy. To see the effect of hormonal contraception on the incidence of obesity in women of childbearing age. The design of this study used descriptive analytic with a cross sectional study approach. The sample in the study were 840 women of childbearing age (15-49 years) who used hormonal contraception (DMPA). Logistic regression analysis was performed to assess the independent factors associated with the incidence of obesity in women of childbearing age using 95% Odds Ratio (OR) and Confidence Interval (CI). P-value < 0.05 was considered statistically significant. Data analysis explained that age, type of hormonal contraception, and duration of contraception use were risk factors for obesity in women of childbearing age. Age > 35 years (OR: 1.6; 95% CI: 0.361-6.807; P 0.548), type of hormonal contraception (OR: 1.8; 95% CI: 1.322-2.461; P <0.001), duration of contraceptive use (OR: 4.9; 95% CI: 3.513-6.851; P <0.001). The type of contraception and the duration of use of hormonal contraception are potential factors for the occurrence of obesity in women of childbearing age. The results of this study help the government to tackle obesity rates.